2019
DOI: 10.1096/fj.201801778rr
|View full text |Cite
|
Sign up to set email alerts
|

Renal phospholipidosis and impaired magnesium handling in high‐fat‐diet–fed mice

Abstract: Hypomagnesemia (blood Mg2+ concentration <0.7 mM) is a common electrolyte disorder in patients with type 2 diabetes (T2D), but the etiology remains largely unknown. In patients with T2D, reduced blood Mg2+ levels are associated with an increased decline in renal function, independent of glycemic control and hypertension. To study the underlying mechanism of this phenomenon, we investigated the renal effects of hypomagnesemia in high‐fat‐diet (HFD)‐fed mice. In mice fed a low dietary Mg2+, the HFD resulted in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…phenomenon in different mouse models of hypomagnesemia (42)(43)(44). This might suggest that compensation of Mg 2+ reabsorption in intestine and kidney might have been initiated in the early treatment phase, resulting in an adapted set-point of Mg 2+ balance.…”
Section: Discussionmentioning
confidence: 98%
“…phenomenon in different mouse models of hypomagnesemia (42)(43)(44). This might suggest that compensation of Mg 2+ reabsorption in intestine and kidney might have been initiated in the early treatment phase, resulting in an adapted set-point of Mg 2+ balance.…”
Section: Discussionmentioning
confidence: 98%
“…Later, two additional patient cohorts were examined: (1) a cohort with isolated tubulopathy and suspected diagnosis of Gitelman syndrome (n558) who had been subjected to WES; and (2) a cohort of patients with dilated cardiomyopathy (n574), in whom mutations in known cardiomyopathy genes had previously been excluded by targeted exome sequencing of 174 cardiovascular genes, including 49 cardiomyopathy genes, as previously described. 17 Cell Lysates and Immunoprecipitation Human embryonic kidney (HEK293T) cells were transfected with Flag-S6K1, RagA, and RagD mutants, as described previously. 15 To determine the response of mechanistic target of rapamycin complex 1 (mTORC1) to amino acid stimulation or starvation under the control of Rag mutants, 2 million HEK293T cells were plated onto a 10-cm dish.…”
Section: Sequencingmentioning
confidence: 99%
“…Previous studies have shown that HFD and Western diet can reduce BMD levels [ 19 , 33 , 34 , 35 , 36 ]. Feeding with HFD may interfere with intestinal mineral absorption and renal reabsorption [ 22 ], especially Mg and Ca [ 21 , 37 ]. This may have decreased bone Ca, P, Mg, and Zn levels in the HFD rats.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, intestinal mineral absorption and mineral homeostasis in kidneys may be interrupted by HFD intake. Then, Ca and Mg metabolisms, which are essential for bone formation, may be disrupted [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%